2023
DOI: 10.3390/horticulturae9020178
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Changes in Berries of “Anab-e-Shahi” and “Perllete” Varieties of Grapes with Advancing Phenology in the Growing Season

Abstract: Understanding how nutrients accumulate and change throughout the developmental stages according to the BBCH scale can be a very effective technique for developing fertilization programmes for high-quality, marketable grape production. Accordingly, the macro- and micronutrient concentrations at different growth stages were analyzed for two commercial grape cultivars, viz., “Anab-e-Shahi” and “Perlette”, by using an extended BBCH scale. The results show nitrogen content was reduced during the sampling period (D1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In the case of vine leaves, the authors of the study reported values greater than one only for Ba under the study conditions, raising caution for food consumption. The content of mineral elements in vine leaves has been analyzed from various perspectives, but more important is the presence of certain elements in relation to the productivity and grape quality [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of vine leaves, the authors of the study reported values greater than one only for Ba under the study conditions, raising caution for food consumption. The content of mineral elements in vine leaves has been analyzed from various perspectives, but more important is the presence of certain elements in relation to the productivity and grape quality [22].…”
Section: Introductionmentioning
confidence: 99%